2014
DOI: 10.1002/j.0022-0337.2014.78.3.tb05692.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Underrepresented Minority and Low–Income High School Students into Dentistry While Educating Dental and Dental Hygiene Students About Academic Careers

Abstract: The objectives of this project were to create a program that would expose underrepresented minority (URM) and low income (LI) high school students to dental professions and provide an opportunity for dental and dental hygiene students from URM/LI groups to be engaged in teaching activities. Data were collected from participants during the school years 2009-10 (high school students: N=23, dental students: N=21, dental hygiene students: N=5) and 2010-11 (N=27, N=11, N=3, respectively). The students participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Mentoring and role modeling in psychology may be often engaged in without deliberate intentions, thus limiting the scope and impact of mentor and role model relationships (Johnson, 2002) Though research has demonstrated that mentors and role models are beneficial (Johnson, 2002), the focus of mentoring literature in psychology has been on graduate training. This is not consistent with literature in other health care fields (Inglehart et al, 2014; Rosenthal, Levy, London, Lobel, & Bazile, 2013), as well as science, technology, engineering, and mathematics fields (Dabneya et al, 2012; Kaye, Berns, Cress, & Nazar, 2014; Sadler, Sonnert, Hazari, & Tai, 2012). Research in these fields has emphasized mentoring relationships in undergraduate and even high school education.…”
Section: Mentors and Role Modelscontrasting
confidence: 91%
“…Mentoring and role modeling in psychology may be often engaged in without deliberate intentions, thus limiting the scope and impact of mentor and role model relationships (Johnson, 2002) Though research has demonstrated that mentors and role models are beneficial (Johnson, 2002), the focus of mentoring literature in psychology has been on graduate training. This is not consistent with literature in other health care fields (Inglehart et al, 2014; Rosenthal, Levy, London, Lobel, & Bazile, 2013), as well as science, technology, engineering, and mathematics fields (Dabneya et al, 2012; Kaye, Berns, Cress, & Nazar, 2014; Sadler, Sonnert, Hazari, & Tai, 2012). Research in these fields has emphasized mentoring relationships in undergraduate and even high school education.…”
Section: Mentors and Role Modelscontrasting
confidence: 91%
“…This curriculum was a collaboration between a tertiary care children's hospital and the local public school system to bring a public health curriculum to 4 high schools. Similar school-based interventions, including programs addressing obesity through gardening and physical fitness 15 and programs aimed at reducing dental disease through education, 16 have successfully targeted public health concerns. Additionally, other schoolbased curricula have been designed to encourage underrepresented minority students to enter professional health fields, such as public health, 17 medical professions, 18 and dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is also supported by the finding that word of mouth and one‐on‐one recruitment efforts were said to be the most effective recruitment practices for these programs. Considering other practices for the recruitment of URM students such as informing students earlier— for example in high school 25 , 26 —and engaging high school counselors more actively 25 should definitely happen as well. In addition, the responses of URM dental hygiene students about their decisions to enroll in these programs reported in Sandino and Rowe's study could be quite helpful in developing specific recruitment approaches 16 …”
Section: Discussionmentioning
confidence: 99%